Construction of mental revolution through State Islamic Higher Education in Indonesia - SAIFULLAH, I; WARUL, W; SULAIMAN, S; MASRIZAL, A; IMRAN, M (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article examines the construction, strategies, and obstacles of mental revolutions at the Islamic higher education in Indonesia. The results of the study found the construction of a mental revolution in the State Islamic University in Indonesia was carried out by the implementation using: Socialization of mental revolution, leadership with integrity, building an environment of integrity, and creating a lecture mention of humanist management, ethical behaviour standards for lectures, mental revolution values in lectures, and mental revolutions. The mental revolution strategy of the State Islamic University in Indonesia is carried out with four strategies, including process with integrity.RESUMEN Este artículo examina la construcción, las estrategias y los obstáculos de las revoluciones mentales en la educación superior islámica en Indonesia. Los resultados del estudio encontraron que la construcción de una revolución mental en la Universidad Estatal Islámica de Indonesia se llevó a cabo mediante la implementación utilizando: Socialización de la revolución mental, liderazgo con integridad, construcción de un entorno de integridad y creación de una mención humanista, manejo, estándares de comportamiento ético para conferencias y revoluciones mentales. La estrategia de revolución mental de la Universidad Estatal Islámica de Indonesia se lleva a cabo con cuatro estrategias, incluido el proceso con integridad.